New biodiversity measure that includes consistent interspecific and intraspecific components. Issue 2 (14th December 2013) - Pavoine, Sandrine; Izsák, Janos; Freckleton, Robert
Summary Current developments of diversity measures that consider that species are not equivalent, concentrate on how functionally or phylogenetically (dis)similar species are from each other (interspecific components). To assess the biodiversity of a community, few of the developed measures include intraspecific components, that is to say components that concern only the current features of the individuals of a species or the history of the species regardless of the other extant species of the community. A requirement for new developments in diversity indices could thus be to integrate both interspecific and intraspecific components. The objectives of our study are to introduce a parametric index of diversity (qH), expressed as an effective number of species, which satisfies this requirement, and to analyse the diversity of order 2 (2H). In the particular case of equal intraspecific components for every species, 2H is a simple function of Rao's quadratic entropy. We introduce our new index family and demonstrate that the vectors of species' proportions that maximize 2H are not necessarily unique and may have zeros (removing species). Then, we apply our index to two case studies: a theoretical example of phylogenetic diversity analysis; and a real data set on the changes in diet diversity of bird communities along an altitudinal gradient. Using a theoretical phylogenetic tree, we demonstrate that a maximizing vector for 2H can be associated with measures of species' phylogenetic originality. Applied to bird communities in Tarentaise Valley, France, 2H describes a decline in diet diversity with altitude due to a higher proportion of invertebrates in the diets of birds that occur where rocks replace deciduous and evergreen bushes and trees. Related to recent developments of diversity study made in the field of ecology, our approach has the advantages of integrating functional or phylogenetic intraspecific and interspecific components, and species' proportions (e.g. relative abundance or biomass), and of being applicable to many different data sets and objectives. Applied to both phylogenetic and functional diversity, our approach can help decisions when prioritizing conservation actions.